PENANAMAN BIBIT POHON SEBAGAI BENTUK KEPEDULIAN TERHADAP LINGKUNGAN DI TWA (TAMAN WISATA ALAM) PANTAI PANJANG BENGKULU - Rahayu, Desita; Reski, Herlinda; Ridianto, Ridianto; Charolina, Ovita; Alfatah, Dhika (Jurnal Semarak Mengabdi, 2023)
One of the steps taken to increase a sense of concern for the environment is to plant tree seeds. The planting was carried out at the Long Beach Bengkulu Nature Park (TWA). The choice of location was based on the condition of the area which was damaged by human activity, including the amount of scattered garbage and the surrounding area which was barren due to community activities which of course had a negative impact on the surrounding environment. The activity which was carried out on October 15 2022 involved the STIA Bengkulu Academic Community and the Bengkulu Natural Resources Conservation Agency (KSDA) by planting Agathis, Durian, Rambutan and Mahogany tree species, which in total totaled 200 tree seeds. The responsibility for the maintenance of this plant is a shared responsibility between MAPALA agra Buana STIA Bengkulu and the Bengkulu KSDA Center. This activity is expected to increase the awareness of the people of Bengkulu City on the importance of protecting and preserving forests, especially in the Nature Tourism Park area.